The demography and disease burden of the homeless shelter population of Tshwane during COVID-19 - Paul S. Germishuys; Selma Smith; Jannie Hugo; Edith Madela-Mntla; Tanita Botha (AOSIS, 2022)
Background: Homeless people are a vulnerable population susceptible to physical and mental health care problems. There are, however, limited studies and information regarding the health of the homeless population. Aim: To describe and understand the burden of disease among the homeless population in Tshwane District, Gauteng, South Africa. Setting: Data were collected from 15 different homeless shelters created during the South African 2020 coronavirus disease 2019 (COVID-19) lockdown in the Tshwane District, from April to July 2020. Methods: A cross-sectional survey was conducted among the homeless people in the shelters to provide information of self-reported conditions that the homeless populations at the shelters had during the lockdown period. The participants were also screened for medical conditions like, human immunodeficiency virus (HIV), hypertension (HPT) and diabetes mellites (DM). Results: Results showed a total of 2066 homeless population out of which 1391 took part in the survey. Most of the participants consisted of African males 93.83%, with substance use prevalence in 52.77%. The study showed that the population was very reluctant to share information and had less chronic conditions than originally thought. Conclusion: Efforts should be made to improve education and research around the homeless population, by government and non-government facilities by building relationships with homeless shelters in their areas. Contribution: This study provides awareness of the homeless population's health and challenges, with the intention to attempt a better understanding of the population that may present themselves to primary healthcare (PHC) facilities and encourage future investigation into how to improve care.